SIFAT ANTIMIKROBA KOMBINASI SENYAWA KIMIA ANTARA EKSTRAK DAUN LIDAH BUAYA (Aloe vera L) DENGAN DAUN SIRIH (Piper bettle L) TERHADAP BAKTERI STREPTOCOCUS MUTANS PENYEBAB DENTAL PLAK - I Gusti Agung Ayu Putu Swastini; I Gusti Agung Ayu Dharmawati; I Gede Surya Kencana; Ni Made Sirat (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
Background: Plants that are medical and used for generations are aloe vera and betel leaf, which contain natural chemical and have antimicrobial and antiseptic properties.Objective: The purpose of this study was to calculate the growth inhibition zone of Streptococcus mutans by using the interaction of aloe vera extract and betel leaf, with a concentration of 50%, 75%, 100%.Method: This research was carried out at the Microbiology Laboratory of Udayana University using a pure experimental method of extracts of Aloe vera leaves and betel leaves with concentrations of 50%, 75%, 100%, seven repetitions, using Streptococcus mutans ATCC 35668, and isolation media for Mueller Hilton plus 5 % goat blood.Results: The average inhibition zone diameter in the interaction groups of aloe vera extract and betel leaf in each group was statistically significant difference (p 0.05), where the inhibitory concentration with the highest 100% concentration was an average of 82.6 mm with very strong criteria.Conclusion: The interaction of aloe vera leaf extract and betel leaf with a concentration of 100% has the highest inhibitory power of 82.6 mm, with very strong criteria.